+23: o trajecto conquistado no ensino superior, análise detalhada dos casos de engenharia na Universidade do Minho - Vasconcelos, Rosa (2010)
The implementation of the Bologna Process in the Portuguese Higher Education system led to a scenario of changes at the education level. The adequacy of the Portuguese higher education system to other European countries has determined, among other measures, the access expansion, especially for new publics. Among others the +23 year old students and Technology Specialization Courses (CET) are considered new public. A survey was carried out, regarding the academic years 2004/2005 through 2008/2009. In order ti understand the academic performance of students entering through the +23 year old students quota courses in Engineering and Technology, of University of Minho. A results analysis was performed education system allows improving the learning/teaching methodologies for this new public. This study analyzes the performance and academic approval of students from their entrance to present.